2011
DOI: 10.1007/s10096-011-1369-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically activated solutions: evidence for antimicrobial efficacy and applications in healthcare environments

Abstract: Due to the limitations associated with the use of existing biocidal agents, there is a need to explore new methods of disinfection to help maintain effective bioburden control, especially within the healthcare environment. The transformation of low mineral salt solutions into an activated metastable state, by electrochemical unipolar action, produces a solution containing a variety of oxidants, including hypochlorous acid, free chlorine and free radicals, known to possess antimicrobial properties. Electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 107 publications
2
98
0
6
Order By: Relevance
“…The high levels of organic load present in the root canals, as in the biofilm structure, particularly in the extracellular polymeric matrix, competitively quenched the reactive oxidants of superoxidized waters that are responsible for its antimicrobial activity (22). Thus, the usual concentration of Sterilox was increased in the present research, trying to overcome this disadvantage.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The high levels of organic load present in the root canals, as in the biofilm structure, particularly in the extracellular polymeric matrix, competitively quenched the reactive oxidants of superoxidized waters that are responsible for its antimicrobial activity (22). Thus, the usual concentration of Sterilox was increased in the present research, trying to overcome this disadvantage.…”
Section: Discussionmentioning
confidence: 94%
“…Lately many studies have shown that the disinfecting actions of super-oxidized waters are heavily reduced by organic contamination (9,15,22). The high levels of organic load present in the root canals, as in the biofilm structure, particularly in the extracellular polymeric matrix, competitively quenched the reactive oxidants of superoxidized waters that are responsible for its antimicrobial activity (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It promotes healing by enhancing local blood supply, accelerating neovascularization, reducing inflammation, improving granulation tissue and epithelialization significantly and producing an environment hostile to opportunistic pathogens, thus reduces morbidity and hospital stay with its early wound healing effect. [2,4,7] Wounds are a great burden on the health-care system and due to the limitations associated with the use of existing biocidal agents, there is a need to explore newer methods of wound care to help maintain effective microbial control, promote early wound healing, reduce hospital stay, and prevent substantial long-term morbidity. [7] …”
Section: Introductionmentioning
confidence: 99%
“…[2,4,7] Wounds are a great burden on the health-care system and due to the limitations associated with the use of existing biocidal agents, there is a need to explore newer methods of wound care to help maintain effective microbial control, promote early wound healing, reduce hospital stay, and prevent substantial long-term morbidity. [7] …”
Section: Introductionmentioning
confidence: 99%